Outcomes of transcatheter edge-to-edge mitral valve repair with percutaneous coronary intervention vs. surgical mitral valve repair with coronary artery bypass grafting - Wang, Xiqiang; Ma, Yanpeng; Liu, Jing; Wang, Ting; Zhu, Ling; Fan, Xiude; Cui, Qianwei; Liu, Chengfeng; Guan, Gongchang; Wang, Junkui; Pan, Shuo; Liu, Zhongwei; et al. (Frontiers in Cardiovascular Medicine, 2022)
Aims: Patients with severe ischemic mitral regurgitation (IMR) may receive concurrent coronary artery bypass graft (CABG) with surgical mitral valve repair (SMVr) or percutaneous coronary stent implantation (PCI) with transcatheter edgeto-edge mitral valve repair (TMVr). However, there is no consensus on the management of severe IMR in this setting. We aimed to compare the outcomes of combined SMVr with CABG to concurrent TMVr with PCI among patients with IMR in National Inpatients Sample (NIS) database. Methods and results: The NIS was queried for all patients diagnosed with ischemic mitral regurgitation (IMR) who underwent SMVr with CABG or TMVr with PCI during the years 2016 to 2018. Study outcomes included all-cause in-hospital mortality, periprocedural complications and resource use. A total of 1360 potentially eligible patients were included in the study. After 1:5 propensity score matching, 133 patients were classified in the SMVr+CABG group and 29 patients in the TMVr+PCI group. Adjusted mortality was higher in the TMVr+PCI group compared with the SMVr+CABG group (13.8% vs 4.5%, P=0.034). Perioperative complications were higher among patients undergoing SMVr+CABG including blood transfusions (29.3% vs 6.9%, P=0.01) and postprocedural cardiogenic shock (11.3% vs 0%, P=0.044). Cost of care was higher (USD$783548.80 vs USD$331846.523, P=0.001), length of stay was longer (17.9 vs 15.44 days, P<0.001) in TMVr+PCI. On multivariable analysis, age (OR, 1.039 [95% CI, 1.006-1.072]; P=0.032), renal failure (OR, 3.465 [95% CI, 1.867-6.433]; P<0.001) and liver disease (OR, 5.012 [95% CI, 2.578-9.686]; P<0.001) were associated with in-hospital mortality. Conclusion: TMVr+PCI was associated with higher resource use, in-hospital mortality, but not associated with improved perioperative complications compared with SMVr+CABG.